Peningkatan Pemahaman Siswa tentang Sistem Pencernaan Manusia dengan Menggunakan Alat Peraga pada Mata Pelajaran IPA di Kelas V SD Negeri 6 Cakranegara - Note, Hafsiahnor Pua (MASALIQ, 2022)
This research began with the low level of students' understanding of the science subject matter of Human Digestive Devices at SD Negeri 6 Cakranegara. The method used by the teacher in the classroom is less innovative and the use of teaching aids is not maximized by the teacher during learning. Teachers only use the lecture method in the learning process, so that student learning outcomes are less than the maximum, only 62.5% of students whose scores are above the KKM. Based on this, teachers need to innovate new learning and increase the use of teaching aids, so as to improve student learning outcomes. This study applies learning by using teaching aids in science subjects for the human digestive tract material so that it helps students make it easier to understand and remember the material being taught. The objectives of this study are: 1) to describe how the application of learning using teaching aids in improving students' understanding in science learning the material of human digestive system for fifth grade students at SD Negeri 6 Cakranegara. 2) describe the increase in the success of the application of learning using teaching aids in improving students' understanding in science learning about the human digestive system material for fifth grade students at SD Negeri 6 Cakranegara. This research was conducted using Kurt Lewin's model consisting of 2 cycles. This research was conducted at SD Negeri 6 Cakranegara with 32 students. Research data obtained by using data collection techniques through observation, interviews, tests and documentation. Based on the results of teacher activity research, student activities and student learning outcomes have increased for the better. The results showed: 1) the application of the use of teaching aids media can increase teacher activity from cycle I 80% in cycle II to 88%. Student activity from the first cycle 66% in the second cycle to 78%. 2) The increase in the percentage of students' learning completeness in the pre-cycle was 62.5%, the first cycle was 84.21% and the second cycle was 89.47%.